2018
DOI: 10.1080/20476965.2017.1414741
|View full text |Cite
|
Sign up to set email alerts
|

Operational research techniques applied throughout cancer care services: a review

Abstract: Cancer is a disease affecting increasing numbers of people. In the UK, the proportion of people affected by cancer is projected to increase from 1 in 3 in 1992, to nearly 1 in 2 by 2020. Health services to tackle cancer can be grouped broadly into prevention, diagnosis, staging, and treatment. We review examples of Operational Research (OR) papers addressing decisions encountered in each of these areas. In conclusion, we find many examples of OR research on screening strategies, as well as on treatment plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…The largest part of the studies addresses the patient appointment scheduling for the infusion activity and the assignment of the daily slots to nurses, focusing on the operational level, rather than tactical or strategic levels (Saville et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The largest part of the studies addresses the patient appointment scheduling for the infusion activity and the assignment of the daily slots to nurses, focusing on the operational level, rather than tactical or strategic levels (Saville et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Carello et al (2021) mention that the literature on outpatient chemotherapy activities is sparse compared to other areas of application with similar features, such as multi-appointment scheduling in healthcare (Marynissen et al 2019). A literature review on operations research techniques applied throughout cancer care services can be found in Saville et al (2019). Moreover, the review paper of Lamé (2016) provides an overview on outpatient chemotherapy planning.…”
Section: Outpatient Chemotherapy Planning and Clinicians Rosteringmentioning
confidence: 99%
“…Operations research (OR) is a discipline that includes a range of techniques aimed at improving decision-making processes in many areas. Combining knowledge from applied mathematics, computer science, and industrial engineering, OR methods such as computer simulation [ 9 ] and mathematical programming [ 10 ] have been widely used to propose solutions for complex real-world problems, including the health care field [ 11 , 12 ]. Recent studies have shown that there is very little scientific reporting on implementation of OR-based algorithms in clinical practice [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%